"Freelance mystic": individuation, mythopoeia and metafiction in the early fiction of Russell Hoban - Rumbold, Matthew Ivan (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2007)
This thesis is an exploration of three interrelated modes - the psychological, the religious or mythopoeic, and the metafictional - in the early novels of Russell Hoban. It investigates the relationship between Hoban's religious vision and his literary style, through the lens of his 'fictional philosophy' as it is presented in his essay collection The Moment under the Moment. In Chapter One, Kleinzeit is analysed to illustrate Hoban's portrayal of a contemporary crisis of meaning. It includes an introduction to the pattern of individuation and an exposition of Hoban's unique notion of heroism as embodied in Kleinzeit's journey of self-discovery. Hoban's mythopoeic impulse is elucidated with particular reference to his use of the Orpheus and Eurydice myth. Finally, in an attempt to demonstrate Hoban's ideas on the relationship between language and reality, various metafictional techniques are examined, especially in relation to the theme of transcendence. In Chapter Two, the individuation theme in The Medusa Frequenry is considered as a work of mourning, portraying Herman Orfrs movement towards reconciliation and creative renewal. Following Paul Ricoeur, the Orpheus and Eurydice myth is seen as a myth of fault, embodying a primal transgression, and a source of the creative arts. The metafictional style is examined, especially the narrative mode, in order to show how Hoban dissolves the everyday world of reality into a fantastic realm of myth. Chapter Three focuses on the individuation pattern as initiation in Riddley Walker, charting the hero's growth into adulthood. Various myths in the text are analysed to show how they portray human development and the nuclear catastrophe as a mythic Fall. The chapter argues that through Riddley's quest Hoban evokes a redemptive and regenerative fertility myth. The unique literary style of the novel, including the characteristics of 'Riddleyspeak' and the complexity of the process of interpretation is studied. In Chapter Four, which deals with Pilgermann, the final phase of individuation - preparation for death - is discussed. Hoban's religious vision is dissected in relation to his mystical impulse as exemplified in the construction of the Hidden Lion pattern. Hoban's notion of God is investigated in relation to the philosophical problem of evil and suffering. Finally, Pilger mann is shown to be Hoban's mOSt experimental literary novel as it activates his recurring meta fictional techniques, investigations into narrative, and the relationship between language and the sacred. This thesis concludes that Hoban's fiction is best understood holistically with both his religious and literary concerns inextricably entwined. Throughout his novels Hoban explores the human condition in modernity affirming the paradoxical, dialectical and mysterious nature of being.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Hoban, Russell -- Criticism and interpretation